THE EFFECT OF OWNERSHIP STRUCTURE ON INTELLECTUAL CAPITAL AND ITS IMPACT ON COMPANY VALUE (A STUDY OF THE BANKING SECTOR ON THE INDONESIA STOCK EXCHANGE 2020-2024 PERIOD) - Frans Atiaqsa; Jacobus Widiatmoko (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of ownership structure, including institutional ownership, foreign ownership, and ownership concentration, on intellectual capital and its impact on firm value in the banking sector on the Indonesia Stock Exchange during the 2020-2024 period. The population used in this study was all banking issuers listed on the Indonesia Stock Exchange during the 2020-2024 period, totaling 47 banks. A purposive sampling method was used to obtain 205 observations, then analyzed using multiple linear regression. The results showed that institutional ownership, foreign ownership, and ownership concentration had a positive effect on intellectual capital, and intellectual capital was proven to influence firm value.